1978
DOI: 10.1071/bi9780553
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Cotton Wool Degrading Strain of Cellulomonas: Mutants With Altered Ability to Degrade Cotton Wool

Abstract: A Cellulomonas strain (CSI-I) which could readily degrade cotton wool was isolated from soil. Production of cell-bound and extracellular carboxymethylcellulase (CMCase), P-glucosidase and avicelase during growth on different substrates was determined. Methods for the isolation of mutants were assessed and mutants were isolated which were altered in their ability to degrade cotton wool when compared to CSI-L Studies on one mutant (CSl-7) which was able to degrade cotton wool more rapidly than the parent reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Cell-bound fj-glucosidases are present in Cellulomonas species (Choi et al, 1978;Stoppok et aI., 1982). These enzymes may be responsible for the hydrolysis of cellobiose to glucose, which then is fermented.…”
Section: Aerobic Cellulolytic Bacteriamentioning
confidence: 98%
See 1 more Smart Citation
“…Cell-bound fj-glucosidases are present in Cellulomonas species (Choi et al, 1978;Stoppok et aI., 1982). These enzymes may be responsible for the hydrolysis of cellobiose to glucose, which then is fermented.…”
Section: Aerobic Cellulolytic Bacteriamentioning
confidence: 98%
“…In addition, several unclassified Cellulomonas isolates are available and are being used in studies of cellulases. These isolates include strain IIbc, obtained in Cuba by Dr. M. Ibarra (Beguin et al, 1977), strain CS 1-1, found in soil (Choi et al, 1978), strain DK, from sludge (Ramasamy et aI., 1981), as well as strains without designations from soil (Han and Srinivasan, 1968;Stewart and Leatherwood, 1976), bagasse (Cabello et ai., 1981), and the gut of a manure worm (Chosson and Dupuy, 1983).…”
Section: Aerobic Cellulolytic Bacteriamentioning
confidence: 99%
“…In strains of Cellulomonas, for example, mutants have been isolated which are more efficient than the parent strains in the degradation of crystalline cellulose. These can be resistant to catabolite repression (Stewart & Leatherwood, 1976), end-product inhibition (Choudhury et al, 1980), or can produce increased levels of cellulases (Choi et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The isolation and characterization of CSl-1 and the mutant derivative CSl-17 have been described previously (Choi et al, 1978;Haggett et al, 1979;Choudhury et al, 1980). The substrate used in these experiments was the fraction of sugar cane bagasse with a particle size less than 0.7 mm.…”
Section: Materials I! Methodsmentioning
confidence: 99%